Single Cell Analysis in Biotechnology and Systems Biology (2020)
Cells are the most fundamental building blocks of most life forms and play a significant role in coordinating with each other to perform systematic functions in all living creatures. However, the behavior of cell to cell, or cell to the environment with their organelles and their intracellular physical and biological functions remains unknown. To better understand the physiological interactions among molecules, organelles, and cells ensemble average measurement of millions of cells together, cannot provide detailed information such as stem cell proliferation, differentiation, neural network coordination, and cardiomyocytes synchronization. Again, biological functions such as genomes, epigenomes and transcriptomes as a bulk population is informative, however it is not enough to understand the cellular heterogeneity characteristics in phenotypic behavior assays and dynamics of individual cells. Thus, single cells analysis (SCA) has evolved in frontier research.